Pyoverdine, the Major Siderophore in Pseudomonas aeruginosa, Evades NGAL Recognition - Mary E. Peek; Abhinav Bhatnagar; Nael A. McCarty; Susu M. Zughaier (Interdisciplinary Perspectives on Infectious Diseases)
Pseudomonas aeruginosa is the most common pathogen that persists in the cystic fibrosis lungs. Bacteria such as P. aeruginosa secrete siderophores (iron-chelating molecules) and the host limits bacterial growth by producing neutrophil-gelatinase-associated lipocalin (NGAL) that specifically scavenges bacterial siderophores, therefore preventing bacteria from establishing infection. P. aeruginosa produces a major siderophore known as pyoverdine, found to be important for bacterial virulence and biofilm development. We report that pyoverdine did not bind to NGAL, as measured by tryptophan fluorescence quenching, while enterobactin bound to NGAL effectively causing a strong response. The experimental data indicate that pyoverdine evades NGAL recognition. We then employed a molecular modeling approach to simulate the binding of pyoverdine to human NGAL using NGAL’s published crystal structures. The docking of pyoverdine to NGAL predicted nine different docking positions; however, neither apo- nor ferric forms of pyoverdine docked into the ligand-binding site in the calyx of NGAL where siderophores are known to bind. The molecular modeling results offer structural support that pyoverdine does not bind to NGAL, confirming the results obtained in the tryptophan quenching assay. The data suggest that pyoverdine is a stealth siderophore that evades NGAL recognition allowing P. aeruginosa to establish chronic infections in CF lungs.